Rancang Bangun Boltheater Electric Dengan Sistem Pengendali Berbasis SMS Controller Untuk Bongkar Pasang Baut Casing Dan Valve Turbin - Jasmid Edy; Retno Aita Diantari; Arman Susanto (JURNAL POWERPLANT, 2014)
The steam turbine generator is the main equipment working at high temperature and pressure so it is very important to do regular maintenance to guarantee keandalannya.Pemliharaan is a simple routine inspection, inspection mean and serious inspection. Serious when turbine maintenance inspection (demolition total) there tubin demolition work and the valve casing turbine in penangananya requires a special instrument called boltheater. The tool is a tool for the disassembly bolt turbine casing and turbine valve with the principle of heating the bolt, causing expansion and further used for disassembling the bolt. Mertode previous boltheater operation is manually which has several shortcomings kekurangan. So to avoid the need for a remote control and one of them is a remote control system based on SMS controller. Automatic control has the advantage of efficient use of personnel which impact on the efficiency of maintenance costs, speed up the process of work (time efficiency) and reduce the risk of workplace accidents during the process of disassembly turbine casing and turbine valve. The existence of the efficiency of the time when the overhaul will increase the chance of generating units operate. Opportunity for all operating units of the plant affects the value of EAF (Equivalent Availability Factor). This is a measure of the success of a plant in the supply and sell electricity.